Vector Penalty-Projection Methods for Open Boundary Conditions with Optimal Second-Order Accuracy (Communications in Computational Physics, 2019)
Recently, a new family of splitting methods, the so-called vector penalty-projection methods (VPP) were introduced by Angot et al. [4, 7] to compute the solution of unsteady incompressible fluid flows and to overcome most of the drawbacks of the usual incremental projection methods. Two different parameters are related to the VPP methods: the augmentation parameter r ≥0 and the penalty parameter 0
Keywords: Vector penalty-projection methods; Navier-Stokes equations; incompressible viscous flows; open boundary conditions; second-order accuracy